Integrated Pest Management : Current Concepts and Ecological Perspective. - Abrol, Dharam P. (Elsevier Science, 2013)
Integrated Pest Management: Current Concepts and Ecological Perspective presents an overview of alternative measures to traditional pest management practices using biological control and biotechnology. The removal of some highly effective broad-spectrum chemicals, caused by concerns over environmental health and public safety, has resulted in the development of alternative, reduced risk crop protection products. These products, less toxic to the environment and easily integrated into biological control systems, target specific life stages or pest species. Predation - recognized as a suitable.